Preaching : communicating faith in an age of skepticism - Keller, Timothy, 1950-2023 (New York : Viking, 2015)
Presents a guide to preaching for pastors as well as laypeople, intended to help readers communicate the Christian message of grace in a meaningful, engaging, and compassionate way.
Preaching the Word -- Preaching the gospel every time -- Preaching Christ from all of Scripture -- Preaching Christ to the culture -- Preaching and the (late) modern mind -- Preaching Christ to the heart -- Preaching and the Spirit.
Includes bibliographical references (pages 241-309).
Keywords: Preaching; Word of God (Christian theology); Communication -- Religious aspects -- Christianity